2013
DOI: 10.5047/eps.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Along-trench structural variation and seismic coupling in the northern Japan subduction zone

Abstract: Large destructive interplate earthquakes, such as the 2011 M w 9.0 Tohoku-oki earthquake, have occurred repeatedly in the northern Japan subduction zone. The spatial distribution of large interplate earthquakes shows distinct along-trench variations, implying regional variations in interplate coupling. We conducted an extensive wide-angle seismic survey to elucidate the along-trench variation in the seismic structure of the forearc and to examine structural factors affecting the interplate coupling beneath the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Significant lateral velocity variations are revealed in the interplate megathrust zone, and most of the large megathrust earthquakes (M ≥ 7.0) which occurred between 1900 and 2013 are situated in or around high-V patches. These results indicate that the rupture nucleation of megathrust earthquakes is controlled by structural heterogeneities in the megathrust zone Zhao 2005, 2006a;Yamamoto et al 2011;Fujie et al 2013a;Huang and Zhao 2013a, b;Moreno et al 2014). A shallow high-V zone with large coseismic slip near the Japan Trench may account for the asperity of the 2011 Tohoku-oki main shock (Mw 9.0).…”
Section: Fore-arc Processesmentioning
confidence: 88%
“…Significant lateral velocity variations are revealed in the interplate megathrust zone, and most of the large megathrust earthquakes (M ≥ 7.0) which occurred between 1900 and 2013 are situated in or around high-V patches. These results indicate that the rupture nucleation of megathrust earthquakes is controlled by structural heterogeneities in the megathrust zone Zhao 2005, 2006a;Yamamoto et al 2011;Fujie et al 2013a;Huang and Zhao 2013a, b;Moreno et al 2014). A shallow high-V zone with large coseismic slip near the Japan Trench may account for the asperity of the 2011 Tohoku-oki main shock (Mw 9.0).…”
Section: Fore-arc Processesmentioning
confidence: 88%
“…This feature is very similar to the results of velocity tomography (Figures d and e) that a significant high‐velocity (high‐ V ) patch exists off Miyagi, whereas low‐ V zones exist off Sanriku, Fukushima, and Ibaraki [e.g., Zhao et al ., ; Huang and Zhao , ; Tian and Liu , ]. Such a pattern of along‐arc velocity and Q variations is also consistent with the results of many two‐dimensional velocity profiles obtained from active‐source seismic experiments near the Japan Trench [e.g., Tsuru et al ., ; Fujie et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on bathymetry changes from before to after the earthquake, Fujiwara et al (2011) demonstrated that the seafloor of the outermost part of the landward trench slope moved approximately 50 m toward the trench and was uplifted by approximately 7 to 10 m. The large fault rupture and propagation might have been due to the essentially weak fault material and dynamic weakening ) and/or abnormal fluid pressure along the megathrust (Kimura et al 2012). Fujie et al (2013) researched the along-trench variation of the structure with seismic surveys in the northern Japan Trench, and their data suggest that there is a good correlation between the seismic structure and segmentation of the interplate coupling. This implies that the variations in the forearc structure are closely related to those in the interplate coupling.…”
Section: Introductionmentioning
confidence: 99%